The Cambridge Handbook of Language Standardization 2021
DOI: 10.1017/9781108559249.028
|View full text |Cite
|
Sign up to set email alerts
|

Standardization and New Urban Vernaculars

Abstract: The authors thank the anonymous reviewers for their critical reading. Special thanks to Gunvor Mejdell, for providing us with many valuable constructive remarks during the writing of this paper. 2 Cfr. also infra §1.2 for a short description of 'contemporary urban vernaculars'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 704 publications
0
4
0
1
Order By: Relevance
“…However, these studies revealed that MSA was not the only prestigious Arabic variety involved given the emergence of prestigious vernaculars, usually linked to varieties of Arabic spoken in major urban centers. Whether old medina dialects or new urban koines, these vernaculars were endowed with higher social status than rural or mountain varieties (see Miller 2007aMiller , 2007bMiller and Falchetta 2021). In fact, as Al-Wer (2002) demonstrated, the more speakers master MSA, the more their linguistic innovations tend to go in the opposite direction, towards the prestigious vernaculars.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, these studies revealed that MSA was not the only prestigious Arabic variety involved given the emergence of prestigious vernaculars, usually linked to varieties of Arabic spoken in major urban centers. Whether old medina dialects or new urban koines, these vernaculars were endowed with higher social status than rural or mountain varieties (see Miller 2007aMiller , 2007bMiller and Falchetta 2021). In fact, as Al-Wer (2002) demonstrated, the more speakers master MSA, the more their linguistic innovations tend to go in the opposite direction, towards the prestigious vernaculars.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite their shared processes, it is important to point out, however, that degrees of koineization and leveling certainly depend on each city's history and on the rate of rural/urban migration. Therefore, there is neither a single model nor a common linear development (Miller & Falchetta, 2021).…”
Section: White Arabic As An Urban Dialectal Koine (And/or a Developin...mentioning
confidence: 99%
“…Currently, as Miller & Falchetta (2021) pointed out, educated speakers of Arabic tend to experience greater mobility and have larger networks, which results in these speakers' increased «exposure to different social values and the need to adopt common features shared by a wider number of people and not indexed with localness» (Miller & Falchetta, 2021, p. 726), this is, the type of features involved in the emergence of urban koines and other accommodative practices (see sections 3.2 and 3.3). For this reason, education represents a key concept for the understanding of WA, and, in general, for the study of any form of accommodation among speakers of Arabic, regardless of its label.…”
Section: Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…En este complejo mosaico de variedades, encontramos variedades prestigiosas -las variedades neo-urbanas (Miller y Falchetta, 2021) y los dialectos de las antiguas medinas-y hablas estigmatizadas -principalmente las de las zonas rurales-. Entre las variedades neo-urbanas podríamos citar el dialecto de Casablanca, considerado por algunos autores (Miller, 2006, pp.…”
Section: Situación Lingüística De Marruecos: Prestigio Y Estigmatizaciónunclassified